Modele systemu finansowego samorządu terytorialnego w wybranych krajach - Miszczuk, Magdalena (Economic inactivity of the working age population in Poland, 2009)
The paper consists of comparative analysis of the levels of economic inactivity of the working age population between Poland and other European countries. The inactivity rate in Poland was much higher in relation to other countries, especially within the youth and older persons. The main reasons for inactivity in Poland include being in education or training and illness and disability. The reasons for inactivity varied markedly between countries.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 199-207